We the people! - Brown, Don, 1949- (Big ideas that changed the world., 2022)
A graphic novel that describes the history of American democracy, and explores how ancient Greek assemblies, the Enlightenment ideals of reason, toleration, and human progress, England's Magna Carta, and the Haudenosaunee (Iroquois) Confederacy inspired the foundation of American democracy. Includes a timeline and additional resources.